Strategy for optimizing information needs survey as the basis for collection development at the University of Timor Library - Mauk, Vincentius; Sau, Palmerya Christina (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. In the digital era, collections must meet university libraires’ user needs. One of the strategies is conducting information needs surveys. This study explores the role and importance of these surveys in collection development at the UPT Library of Timor University. Research Method. A qualitative approach was used, with data gathered through participatory observation, interviews, and recordings from purposively selected informants. Data Analysis. Data analysis was conducted by following Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. Results and Discussion. The study shows that information needs surveys are vital to aligning collections to meet user needs. However, challenges exist, such as limited librarian competence, budget constraints, and lack of coordination between library staff and users. Conclusion and Recommendations. Information needs surveys play a strategic role in collection development at Timor University Library. Optimizing their implementation through systematic and continuous processes is necessary to improve collection relevance, evaluation effectiveness, and support the library’s academic function. The optimization of collection development requires systematic surveys, librarian competence enhancement, good coordination, and regular collection evaluations.